Crown lengthening procedure following intentional endodontic therapy for correction of supra-erupted posterior teeth: Case series with long-term follow-up - Shruti Arun Patil; Sudhindra Kulkarni; Srinath Thakur; Balaram Naik (Wolters Kluwer Medknow Publications, 2016)
Context: The crown lengthening procedure (CLP) is routinely carried out to correct gingival levels and achieve esthetic contours and adequate crown lengths for restorative purposes. Though the short-term outcomes have been found to be stable, long-term results are not much reported. Aims: To evaluate the long-term stability of the marginal bone levels, gingival levels, and the status of the teeth, which underwent endodontic therapy, followed by CLP and final restorations. Settings and Design: Institutional setting, long-term case series. Materials and Methods: Case records of the patients who underwent CLP and endodontic therapy for corrections of the supra-erupted teeth to regain the lost interocclusal spaces were retrieved, and the cases with complete set of the clinical and radiographs were taken. All the cases were recalled and bone levels on the radiographs, bleeding on probing, probing pocket depths, and changes in the soft tissue margins were evaluated. Statistical Analysis Used: Descriptive analysis. Results: A total of 25 teeth had undergone CLP and endodontic therapy and final restorations for a minimum of 24 months. The mean post-restorative duration was 50.8 ± 22.48 months (range 24-96 months). All the teeth were functional and asymptomatic with 100% survival. Interdental bone loss of 1 mm, probing pockets of 5 mm, and 1 mm buccal recession were observed in 16% of the sites. The amount of interocclusal space regained was adequate to restore the missing teeth in the opposing arch. Conclusions: The CLP is a predictive procedure for correction of supra-erupted teeth. The survival of the teeth that underwent the procedure in the present study was 100% over 24-96 months.